Healthper: Healthy Diet Mobile Application - So Shyuan, Meagan; Wahid, Norfaradilla (Applied Information Technology And Computer Science, 2021)
A healthy diet is important because eating a variety of food that gives nutrients help to maintain health, feel good and have energy. These nutrients include protein, carbohydrate, fat, water, vitamin, and minerals. Many mobile applications are ready to use. However, the challenges faced by these applications was it need user’s experience in long run and it might bring wrong information for users and it does not have monitoring and tailored services for each user based on their health condition. To solve this problem, an application was developed to be an intermediate tool for user and professionals. It will have a food habit tracker that enables the user to understand their food habit better. A sharing platform for both user and professional to share their knowledge and experience was provided. The prototype model is used in the development of this project. It is a software development model in which a prototype is built, tested and reworked until an acceptable prototype is achieved. This application is developed as an Android Operating System mobile application by using Android Studio and Firebase as a cloud storage platform.